Life-Threatening Protein-Losing Enteropathy Due To Human Cytomegalovirus Infection Upon Immunochemotherapy - Maria, Fratta Pasini Anna; Carlo, Visco; Elisa, Dalla Grana; Costanza, Fraenza; Marco, Bodini; Sara, Pecori; Cristina, Conti Bellocchi Maria; Niccolò, Faccioli; Antonio, Piralla; Domenico, Girelli; et al. (Archives of Clinical and Medical Case Reports, 2021)
Immunochemotherapy adverse events affecting the gastrointestinal tract usually consist of self-limiting nausea/ vomiting or diarrhoea, while bleeding and perforation are rare. A 42-year-old woman treated with bendamustine/ rituximab for splenic marginal zone lymphoma developed a life-threatening protein-losing enteropathy that was a diagnosis conundrum, ranging from drug-induced, immunemediated, neoplastic and infectious forms. Suspecting opportunistic viral infection but with unremarkable immunohistochemistry and peripheral blood tests, the diagnosis of Human Cytomegalovirus enteritis was made only by means of quantitative real-time polymerase chain reaction carried out on mucosal specimens. Steroid discontinuation and a prolonged course of antiviral therapy allowed the patient to overcome the critical phase and to achieve gradual normalisation of stool frequency, body mass index, laboratory tests lasting one year, while disappearance of mucosal viral load resulted soon evident. Human Cytom-egalovirus end-organ disease localised at the gastrointestinal tract is a serious condition whose prompt diagnosis and treatment prevents poor patients prognosis.